Ediciós do Castro and Editorial Cuco-Rei (1963-1978) - Pérez Rodríguez, María Antonia (Madrygal. Revista de Estudios Gallegos, 2015)
This is an analysis of two publishing companies: O Castro and Cuco-Rei. We shall look at their commercial relationship as well as their dealings with the Sargadelos business group. We shall also examine their editorial line and correspondence with exiled Galician publishers in Buenos Aires, paying particular attention to those led by Seoane. This analysis also shows how O Castro was characterised by its editorial line that began to develop from 1963 to 1978, and which consisted in showing the work of the Seminario de Estudos Galegos and in recuperating Galician historical memory.
Keywords: Ediciós do Castro; Editorial Cuco-Rei; Grupo Sargadelos; historical memory; exile in Argentina; artist books